Geolocation web application for vehicule routing problem based on genetic algorithms - Bounif, Issam (FACULTE DES MATHEMATIQUES ET DE L’INFORMATIQUE - UNIVERSITE MOHAMED BOUDIAF - M’SILA, 2016)
In the industry field The challenging strategy of supply chain management and logistics is to optimize the product delivery from suppliers to customers thus satisfying constraints. Such problems are known as Vehicle Routing Problems (VRP), in which the vehicles leave the depot, serve customers assigned and upon completion of their routes return to the depot. In this thesis, our goal is to minimize the distance travelled by applying the bio-inspired Genetic Algorithms. After that our solution is implemented through a web application and to increase the challenges we will create an android application for the management of our system .
Keywords: Vehicle Routing Problems, optimization, Genetic Algorithms